The Influence of Breastfeeding Self-Efficacy Education on Pregnant Women's Attitudes Towards Exclusive Breastfeeding at Aura Syifa Hospital, Kediri Regency - Ely Isnaeni; Yanuar Pujiastutik; Sheylla Septina Margareta; Paramita Ratna Gayatri; Erik Irham Lutfi (Journal Of Nursing Practice, 2026)
Background: Feeding babies only breast milk is very important for lowering health problems in infants and helping them develop properly. However, coverage remains suboptimal. Breastfeeding Self-Efficacy (BSE) plays a big role in how successful breastfeeding is. When mothers don't feel confident, they often have negative attitudes that can make breastfeeding harder. Initial research showed that 70% of pregnant women did not have positive views about exclusively breastfeeding, highlighting the need for educational programs based on BSE. Objective: This study aimed to find out how BSE education influences pregnant women’s views on exclusive breastfeeding. Methods: A study was carried out at RS Aura Syifa using a one-group pretest-posttest design, which means that we tested the same group of people before and after an intervention. A group of 50 pregnant women was chosen using No probability sampling with accidental sampling. The program included weekly video lessons given over two weeks, using both in-person and online methods. Data were analyzed using Wilcoxon. Results: The study showed that there was a noticeable change for the better in how people felt after the intervention. The statistical analysis showed a p-value of 0.000 (p < 0.05), which means that BSE education had a significant impact on the attitudes of pregnant women. Conclusion: Teaching pregnant women about breastfeeding confidence helps them have a better attitude towards exclusive breastfeeding. Health care providers should include education about Breastfeeding Self-Efficacy (BSE) in prenatal care. Future researchers should look into other factors like family support or breastfeeding practices.